2021
DOI: 10.51559/jcmid.v1i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral mechanisms targeting regulatory genes Tat and Rev to defeat latent HIV-1 infected T cells: a literature review

Abstract: Antiviral drug therapies have been utilized to prevent disease progression in patients positive HIV-1. Various research has been conducted to investigate and develop a potential functional therapy to suppress HIV-1 replication and cure latent HIV-1 in the absence of drugs. Approaches that have been well studied are the anti-HIV-1 which targets RNAs, proteins, or peptides expressed by HIV-1 resistant cells, which can be transplanted to the patients. RNA interference in the form of small RNA has been proven as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…showed that tropism of adenoviruses depends on the host cell receptors to which they can attach, and it can be further enhanced with different techniques. 94 Because adenoviruses can be easily produced in high concentrations, they can be used in gene and cancer therapies, as well as in vaccine development. 95 Recently, more attention has been paid to combination therapies using adenoviruses and other oncolytic viruses with a chemotherapeutic agent (e.g., paclitaxel).…”
Section: Introductionmentioning
confidence: 99%
“…showed that tropism of adenoviruses depends on the host cell receptors to which they can attach, and it can be further enhanced with different techniques. 94 Because adenoviruses can be easily produced in high concentrations, they can be used in gene and cancer therapies, as well as in vaccine development. 95 Recently, more attention has been paid to combination therapies using adenoviruses and other oncolytic viruses with a chemotherapeutic agent (e.g., paclitaxel).…”
Section: Introductionmentioning
confidence: 99%